(3JhVjM GdcdGe aj TQM TQGFY GdGSdGes - (3eMeO Hf YHO Gddg Hf eMeO Hf CMeO Hf eXaQ GdfLaj,J (B1322 (3g` s
(3ChdgG (B:s
(3hHYO agPG GdeLdO GdKGfi ef JhVjM GdcdGe cJGH GdVeGf s
(3BNQgG (B:s
(3ceG SHb ai GdehGQjK dc HTcd HGf XGgQ GdGLfGS GNJUGU GdYbd HGdeSde ddeSde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B244s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI GdchaI (B(5) s
Keywords: (3abg GdePGgH GdCNQis